Faktor Penentu Audit Report Lag Pemerintah Daerah di Indonesia - Wicaksono, Aditya Kurniawan; sutaryo, sutaryo (Faculty of Economic and Business, 2017)
The Determine Factors of Audit Report Lag at Local Government in IndonesiaThis study aims to determine the effect of internal audit and the assistance of state development audit agency (BPKP) to audit report lag (ATR) at 330 local governments in Indonesia in 2013. Internal audits are proxied with the sufficiency of the number of internal auditors and the number of internal auditors that the local government has indicated, while the assistance of BPKP is projected by the implementation of the information system. This research is able to give a result that sufficient number of internal auditor, number of trained internal auditor, implementation of information system implementation have negative effect to audit report lag It is also important to implement a reliable system of financial management in order to make the financial management process more accountable and transparent.DOI: 10.15408/ess.v7i2.5199